Battery
By using electrolytic zinc foil as the negative electrode active material layer in the battery, the gas generation problem caused by zinc corrosion is solved, and the storage characteristics and capacity stability of the battery are improved.
Patent Information
- Application Number
- CN202411696071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-08
- Filing Date
- 2020-02-07
- Publication Date
- 2025-02-18
AI Technical Summary
In batteries using zinc or zinc alloys as negative electrode active substances, corrosion of zinc causes gas production in the battery, reducing the storage properties of the battery, especially in the long-term storage, there is room for improvement.
Using electrolytic zinc foil as the negative electrode of the active material layer, the generation of gas in the battery is more easily suppressed than rolled zinc foil. The electrolytic zinc foil can be composed of zinc or zinc alloy and its performance is optimized by adding elements such as Bi and In.
By using electrolytic zinc foil as the negative electrode active material layer, the storage characteristics of the battery are significantly improved, gas generation is reduced, the battery capacity is prevented, and the productivity of the negative electrode and the flexibility formed into a sheet are optimized.
Smart Images

Figure CN119481122A_ABST
Abstract
Description
[0001] The present invention is a divisional application of the invention application with application number 202080012293.9 (international application number PCT / JP2020 / 004763), application date February 7, 2020, and invention name “Negative electrode and sheet battery for aqueous electrolyte battery”. Technical Field
[0002] The present application relates to a negative electrode suitable for an aqueous electrolyte battery such as an air battery and a sheet battery having the negative electrode. Background Art
[0003] Batteries using zinc or zinc alloy in the negative electrode, such as air batteries and alkaline batteries, are generally button-shaped batteries using a metal can as an outer body, or cylindrical batteries using a cylindrical outer can.
[0004] On the other hand, a battery having a negative electrode as described above can also be made into a sheet-shaped battery using an outer body made of a resin film (Patent Document 1, etc.). In the sheet-shaped battery described in Patent Document 1, zinc or zinc alloy used as the negative electrode can be used in a form of a foil in addition to a particle form.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 056307 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] However, in batteries using zinc or zinc alloy as negative electrode active materials, gas is easily generated in the battery due to zinc corrosion, which causes the storage performance of the battery to decrease. Although zinc in the form of foil is more likely to suppress gas generation than in the case of particles, there is still room for improvement in long-term storage performance.
[0010] The present application has been made in view of the above circumstances, and provides a sheet battery having excellent storage characteristics and a negative electrode that can constitute the sheet battery.
[0011] Solutions to the problem
[0012] The negative electrode for aqueous electrolyte battery disclosed in the present application is characterized in that it contains electrolytic zinc foil as an active material layer. It should be noted that the electrolytic zinc foil referred to in this specification includes electrolytic foil composed of zinc (and inevitable impurities) and electrolytic foil composed of zinc alloy.
[0013] In addition, the sheet battery disclosed in the present application is characterized in that it includes a sheet-like outer casing and a power generation element accommodated in the above-mentioned sheet-like outer casing, and the above-mentioned power generation element includes a positive electrode, a negative electrode, a separator and an aqueous electrolyte, and the above-mentioned negative electrode is a negative electrode for the aqueous electrolyte battery disclosed in the above-mentioned present application.
[0014] Effects of the Invention
[0015] According to the present application, it is possible to provide a sheet-shaped battery having excellent storage characteristics and a negative electrode that can constitute the sheet-shaped battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] [ Figure 1 ] Figure 1 It is a plan view schematically showing an example of a negative electrode for an aqueous electrolyte battery according to an embodiment.
[0017] [ Figure 2 ] Figure 2 It is a plan view schematically showing an example of a sheet battery according to an embodiment.
[0018] [ Figure 3 ] Figure 3 yes Figure 2 II line cross-sectional view.
[0019] [ Figure 4 ] Figure 4 This is a graph showing the results of a gas generation measurement test of the electrolytic zinc foil and the rolled zinc foil in the examples.
[0020] [ Figure 5 ] Figure 5 This is a graph showing the results of a discharge characteristic evaluation test of the sheet-shaped air battery in the example. DETAILED DESCRIPTION
[0021] (Aqueous electrolyte battery negative electrode)
[0022] An embodiment of the negative electrode for an aqueous electrolyte battery disclosed in the present application will be described. The negative electrode of this embodiment is used for a battery having an aqueous electrolyte and has an active material layer composed of an electrolytic zinc foil.
[0023] Zinc foil (including zinc alloy foil) has different manufacturing methods such as rolled zinc foil and electrolytic zinc foil. According to the research of the present inventors, it is found that when electrolytic zinc foil is used as the active material layer of the negative electrode, it is easier to suppress the generation of gas caused by zinc corrosion in the battery than when rolled zinc foil is used. Although the reason is not certain, it is speculated that it may be because the grain state (crystal particle size, etc.) of the metal (or alloy) in the electrolytic zinc foil and the rolled zinc foil is different, especially when the added elements are contained, the added elements are easier to be evenly distributed in the electrolytic zinc foil than in the rolled zinc foil.
[0024] In this way, the negative electrode of this embodiment can suppress the generation of gas in the battery, so by using it in a battery with an aqueous electrolyte, its storage characteristics can be improved. In addition, since the consumption of Zn (zinc) that functions as a negative electrode active material due to corrosion that does not participate in the discharge reaction can be suppressed, the reduction of battery capacity can also be prevented.
[0025] On the other hand, in the case of electrolytic zinc foil containing additive elements, depending on the type of additive elements, the foil may become harder and more brittle than rolled zinc foil, and thus, problems such as cracking of the foil may occur during the manufacture of the negative electrode, etc. That is, the appropriate method (composition of zinc alloy, etc.) when using electrolytic zinc foil for the negative electrode is considered to be different from that of rolled zinc foil.
[0026] The electrolytic zinc foil may be made of Zn (and inevitable impurities) or a Zn alloy, but is preferably made of a Zn alloy containing an additive element, for example, from the viewpoint of being able to more effectively suppress the generation of gas in the battery.
[0027] The Zn alloy constituting the electrolytic zinc foil preferably contains Bi from the viewpoint of the effect of suppressing the generation of gas.
[0028] From the viewpoint of better ensuring the above-mentioned effect brought about by containing Bi, the proportion of Bi in the Zn alloy constituting the electrolytic zinc foil is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, and most preferably 0.02 mass% or more. However, if the Bi content increases, the reaction resistance of the negative electrode during discharge increases, the operating voltage of the battery decreases, or the effect of suppressing gas generation decreases. Therefore, the proportion of Bi in the Zn alloy constituting the electrolytic zinc foil is preferably 0.2 mass% or less, more preferably 0.1 mass% or less, and most preferably 0.07 mass% or less.
[0029] In addition, in the case of zinc particles, In is also generally used as an additive element because it helps to suppress the generation of gas in the negative electrode in the battery in the same way as Bi. However, In also has the effect of increasing the hardness of the electrolytic zinc foil, so if the amount of In in the Zn alloy is too much, the formed foil becomes hard and brittle, and there is a concern that the productivity of the negative electrode and the flexibility of the battery formed into a sheet will be damaged. Therefore, the electrolytic zinc foil does not contain In, or when In is contained, the proportion of In in the Zn alloy constituting the electrolytic zinc foil is preferably 0.04 mass% or less, and more preferably 0.02 mass% or less.
[0030] Electrolytic zinc foil may contain Al, Mg, Ca, Sr, etc. as additive elements (alloy elements) other than Bi and In. The total proportion of alloy elements other than Bi and In in the Zn alloy is preferably 0.1 mass % or less, more preferably 0.05 mass % or less.
[0031] The thickness of the electrolytic zinc foil is, for example, preferably 10 μm or more, more preferably 30 μm or more, from the viewpoint of discharge capacity; and preferably 1000 μm or less, more preferably 500 μm or less, from the viewpoint of flexibility.
[0032] The electrolytic zinc foil constituting the negative electrode of the present embodiment can be an electrolytic zinc foil manufactured by a conventionally known method. Electrolytic zinc foil generally has a smaller crystal grain size than rolled zinc foil, and the side in contact with the electrode drum (the side opposite to the plating side) tends to be smoother than the plating side, so it can be distinguished from rolled zinc foil by SEM (scanning electron microscope) observation, surface roughness measurement, etc.
[0033] The negative electrode of this embodiment has, for example, a main body portion made of electrolytic zinc foil that functions as a negative electrode active material layer, and can be manufactured by attaching a lead portion for connecting to a negative electrode external terminal of a battery (a terminal of a negative electrode for connecting to an instrument using the battery) to the main body portion by welding, etc. as needed. Alternatively, the negative electrode may be manufactured by attaching the negative electrode external terminal of the battery itself to the main body portion made of electrolytic zinc foil by welding, etc., instead of the lead portion.
[0034] The lead part and the negative electrode external terminal of the battery can be made of, for example, a foil (plate), a wire, etc. made of a metal exemplified below as a material that can constitute a negative electrode current collector. When the lead part of the negative electrode and the negative electrode external terminal are foils (plates), the thickness is preferably 20 μm or more and 500 μm or less. In addition, when the lead part of the negative electrode and the negative electrode external terminal are wires, the diameter is preferably 50 μm or more and 1500 μm or less.
[0035] The lead portion and the negative electrode external terminal of the battery may be made of materials other than metal materials as long as they have conductivity, and a carbon material may be used, or they may be formed by applying a carbon paste and drying it.
[0036] In addition, the negative electrode may be formed from a single sheet of electrolytic zinc foil by cutting the electrolytic zinc foil into a shape having a main body, a lead portion, and a negative electrode external terminal, or a battery may be constructed using a negative electrode in which the main body, the lead portion, and the negative electrode external terminal are integrally formed from the same electrolytic zinc foil. From the perspective of further improving the productivity of the negative electrode, it is more preferable to manufacture the negative electrode by cutting a single sheet of electrolytic zinc foil into a shape having a main body, a lead portion, and a negative electrode external terminal.
[0037] Figure 1 2 is a plan view schematically showing an example of the negative electrode according to the present embodiment. Figure 1The negative electrode 10 shown in FIG. 1 includes a main body 11 functioning as a negative electrode active material and a negative electrode external terminal 12 , and the main body 11 and the negative electrode external terminal 12 are formed of a single electrolytic zinc foil.
[0038] In addition, a current collector may be used in the negative electrode as needed. Examples of the current collector for the negative electrode include mesh, foil, expanded metal, punched metal of metals such as nickel, copper, and stainless steel; and sheets and meshes of carbon. The thickness of the current collector for the negative electrode is preferably not less than 10 μm and not more than 300 μm.
[0039] (Sheet battery)
[0040] The sheet battery of the present invention has a sheet-shaped outer casing and a power generation element contained in the sheet-shaped outer casing, wherein the power generation element includes a positive electrode, a negative electrode, a separator and an aqueous electrolyte, and the negative electrode for aqueous electrolyte battery disclosed in the present invention is used as the negative electrode.
[0041] The sheet battery of this embodiment can be in the form of various batteries (alkaline batteries (alkaline primary batteries, alkaline secondary batteries), manganese batteries, air batteries, etc.) having an aqueous electrolyte (i.e., an electrolyte formed of an aqueous solution using water as a solvent).
[0042] Hereinafter, regarding the sheet-like battery of the present embodiment, the power generation elements other than the negative electrode and the sheet-like exterior body will be described.
[0043] <Positive electrode>
[0044] When the sheet-shaped battery is an alkaline battery or a manganese battery, the positive electrode may have a structure in which a positive electrode mixture layer containing a positive electrode active material, a conductive auxiliary agent and a binder is provided on one or both sides of a current collector.
[0045] Examples of positive electrode active materials that can be used when the battery is an alkaline battery include silver oxide (silver monoxide (first silver oxide), silver monoxide (second silver oxide), etc.); manganese oxides such as manganese dioxide; nickel oxyhydroxide; composite oxides of silver and cobalt, nickel or bismuth, etc. In addition, manganese oxides such as manganese dioxide can be used as the positive electrode active material when the battery is a manganese battery.
[0046] The conductive aid in the positive electrode mixture layer includes, in addition to carbon blacks such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; carbon materials such as carbon fibers, conductive fibers such as metal fibers; carbon fluoride; metal powders such as copper and nickel; and organic conductive materials such as polyphenylene derivatives.
[0047] Examples of the binder in the positive electrode mixture layer include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polyvinyl pyrrolidone (PVP).
[0048] The composition of the positive electrode mixture layer is preferably 80 to 98% by mass of the positive electrode active material, 1.5 to 10% by mass of the conductive aid, and 0.5 to 10% by mass of the binder. In addition, the thickness of the positive electrode mixture layer (thickness per single side of the collector) is preferably 30 to 300 μm.
[0049] A positive electrode having a positive electrode mixture layer can be manufactured, for example, by the following process: a positive electrode active material, a conductive aid, a binder, etc. are dispersed in water or an organic solvent such as N-methyl-2-pyrrolidone (NMP) to prepare a composition (slurry, paste, etc.) containing the positive electrode mixture (the binder can also be dissolved in the solvent), applied to a current collector and dried, and subjected to a pressing treatment such as calendering as needed.
[0050] When the battery is an air battery, the positive electrode (air electrode) may include a positive electrode having a catalyst layer, for example, a positive electrode having a structure in which a catalyst layer and a current collector are stacked.
[0051] The catalyst layer may contain a catalyst, a binder, and the like.
[0052] As the catalyst in the catalyst layer, for example, silver, platinum group metals or alloys thereof; transition metals; Pt / IrO 2 etc.Pt / metal oxides; La 1-x Ca x CoO 3 Perovskite oxides, WC carbides, Mn 4 Nitrides such as N; manganese oxides such as manganese dioxide; carbon (graphite, carbon black (acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.), charcoal, activated carbon, etc.), etc., and one or more of them can be used.
[0053] It should be noted that the heavy metal content of the catalyst layer is preferably less than 1% by mass. The sheet-shaped battery of this embodiment can be easily destroyed by tearing it by hand when it is discarded. When it is a positive electrode having a catalyst layer with a low heavy metal content as described above, it can be made into a battery with a small environmental load even if it is discarded without special treatment.
[0054] The content of heavy metals in the catalyst layer mentioned in this specification can be measured by fluorescent X-ray analysis. For example, the fluorescent X-ray analyzer "ZSX100e" manufactured by Rigaku Corporation can be used with an excitation source of Rh50kV and an analysis area of The measurement was carried out under the conditions of .
[0055] Therefore, it is preferred that the catalyst in the catalyst layer contain no heavy metal, and it is more preferred to use the above-mentioned various carbons.
[0056] In addition, from the viewpoint of further improving the reactivity of the positive electrode, the specific surface area of the carbon used as the catalyst is preferably 200 m 2 / g or more, more preferably 300m 2 / g or more, more preferably 500m 2 / g or more. The specific surface area of carbon mentioned in this specification is a value obtained by the BET method based on Japanese Industrial Standard (JIS) K 6217. For example, it can be measured using a specific surface area measuring device based on the nitrogen adsorption method ("Macsorb HM modele-1201" manufactured by Mountech). It should be noted that the upper limit of the specific surface area of carbon is usually 2000m 2 / g or so.
[0057] The content of the catalyst in the catalyst layer is preferably 20 to 70% by mass.
[0058] As the binder in the catalyst layer, PVDF, PTFE, copolymers of vinylidene fluoride, copolymers of tetrafluoroethylene (vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), vinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), vinylidene fluoride-tetrafluoroethylene copolymer (PVDF-TFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer (PVDF-HFP-TFE) etc.) and other fluororesin binders are listed. Among them, polymers (PTFE) or copolymers of tetrafluoroethylene are preferred, and PTFE is more preferred. The content of the binder in the catalyst layer is preferably 3 to 50% by mass.
[0059] In the case of a positive electrode having a catalyst layer, for example, the above-mentioned catalyst, binder, etc. can be mixed with water and rolled by a roller to make it close to the collector. In addition, the above-mentioned catalyst and the binder used as needed can be dispersed in water or an organic solvent to prepare a catalyst layer forming composition (slurry, paste, etc.), which is applied to the surface of the collector and dried, and then manufactured through a pressing process such as a calendering treatment implemented as needed.
[0060] In addition, a porous carbon sheet made of fibrous carbon such as carbon paper, carbon cloth, or carbon felt may be used as the catalyst layer. The carbon sheet may also be used as the positive electrode current collector described below, or may be used as both.
[0061] The current collector in the positive electrode having the positive electrode mixture layer and the positive electrode having the catalyst layer may be, for example, a mesh, foil, expanded metal mesh, punched metal of a metal such as titanium, nickel, stainless steel, copper, or a carbon mesh, sheet, etc. The thickness of the current collector in the positive electrode is preferably 10 μm to 300 μm.
[0062] In addition, the current collector of the positive electrode can also utilize a part of the resin film constituting the sheet-like outer package. In this case, for example, a carbon paste is applied to the surface of the resin film that is intended to become the inner surface of the sheet-like outer package as a current collector, or the metal layer of the resin film having a metal layer is used as a current collector, and a positive electrode mixture layer and a catalyst layer are formed on the surface of the current collector in the same manner as described above, thereby making a positive electrode. The thickness of the above-mentioned carbon paste layer is preferably 30 to 300 μm.
[0063] The positive electrode usually has a positive electrode external terminal. The positive electrode external terminal can be formed by connecting an aluminum foil (plate) or wire, a nickel foil (plate) or wire, etc. to the collector of the positive electrode via a lead body, or directly connecting to the collector of the positive electrode. When the positive electrode external terminal is a foil (plate), the thickness is preferably 50 μm or more and 500 μm or less. In addition, when the positive electrode external terminal is a wire, the diameter is preferably 100 μm or more and 1500 μm or less.
[0064] Alternatively, a portion of the current collector may be exposed to the outside to serve as a positive electrode external terminal.
[0065] <Diaphragm>
[0066] In sheet batteries, a separator is placed between the positive electrode and the negative electrode. When the battery is an alkaline battery, a manganese battery, or an air battery, the separator can be a non-woven fabric based on vinylon and rayon, a vinylon-rayon non-woven fabric (vinylon-rayon blended paper), a polyamide non-woven fabric, a polyolefin-rayon non-woven fabric, a vinylon paper, a vinylon-cotton linter pulp paper, a vinylon-mercerized pulp paper, etc. In addition, a microporous film can also be used, specifically a microporous polyolefin film (microporous polyethylene film, microporous polypropylene film, etc.), and in order to improve the wettability with the aqueous electrolyte, a hydrophilic treatment can also be applied to its surface.
[0067] In addition, the above-mentioned microporous film can be overlapped with a liquid absorbing layer (electrolyte retaining layer) such as a cellophane film and a vinylon-rayon blended paper to form a separator. The thickness of the separator is, for example, preferably 10 to 500 μm, preferably 10 to 50 μm in the case of a microporous film, and preferably 20 to 500 μm in the case of a nonwoven fabric.
[0068] <Electrolyte>
[0069] The electrolyte of the sheet battery uses an aqueous electrolyte using water as a solvent. It should be noted that the pH of the aqueous electrolyte is preferably less than 12 from the viewpoint of reducing the environmental load when discarded, and is more preferably less than 7 from the viewpoint of being able to better ensure the effect brought about by using the negative electrode of this embodiment. In addition, in order to prevent corrosion of the electrolytic zinc foil, the pH of the aqueous electrolyte is usually preferably 3 or more, and more preferably 4 or more. However, when the sheet battery is an alkaline battery, the pH of the aqueous electrolyte can be increased to 12 or more, and can also be, for example, 14 or more.
[0070] When the sheet battery is an alkaline battery, an alkaline electrolyte can be used as an aqueous electrolyte. That is, an alkaline aqueous solution formed by an aqueous solution of an alkali metal hydroxide such as potassium hydroxide, sodium hydroxide, lithium hydroxide, or an alkaline aqueous solution to which zinc oxide is added can be used. The concentration of the alkali metal hydroxide in the alkaline electrolyte is preferably 28 to 38% by mass when potassium hydroxide is used, and preferably 1.0 to 4.0% by mass when zinc oxide is used.
[0071] When the sheet-shaped battery is an air battery or a manganese battery, as the aqueous electrolyte, an aqueous solution obtained by dissolving an electrolyte salt or the like in water can be used. Examples of the electrolyte salt include chlorides such as sodium chloride, potassium chloride, magnesium chloride, calcium chloride, ammonium chloride, and zinc chloride; hydroxides of alkali metals and alkaline earth metals (sodium hydroxide, potassium hydroxide, magnesium hydroxide, etc.), acetates thereof (sodium acetate, potassium acetate, magnesium acetate, etc.), nitrates thereof (sodium nitrate, potassium nitrate, magnesium nitrate, etc.), sulfates thereof (sodium sulfate, potassium sulfate, magnesium sulfate, etc.), phosphates thereof (sodium phosphate, potassium phosphate, magnesium phosphate, etc.), borates thereof (sodium borate, potassium borate, magnesium borate, etc.), citrates thereof (sodium citrate, potassium citrate, magnesium citrate, etc.), glutamates thereof (sodium glutamate, potassium glutamate, magnesium glutamate, etc.); bicarbonates of alkali metals (sodium bicarbonate, potassium bicarbonate, etc.); percarbonates of alkali metals (sodium percarbonate, potassium percarbonate, etc.); halogen-containing compounds such as fluorides; polycarboxylic acids, etc. The aqueous electrolyte solution may contain one or more of these electrolyte salts.
[0072] When the sheet battery is an air battery, as described above, the pH of the aqueous electrolyte is preferably less than 12 (more preferably less than 7). When an electrolyte salt that changes the pH is used when preparing an aqueous solution to form the aqueous electrolyte, its concentration is preferably adjusted so that the pH of the aqueous electrolyte becomes the above-mentioned value.
[0073] When the sheet-shaped battery is an air battery, the aqueous electrolyte is preferably an aqueous chloride solution such as a sodium chloride aqueous solution. For example, when the sodium chloride aqueous solution is used, the concentration of the sodium chloride is preferably 1 to 23% by mass.
[0074] It should be noted that when the sheet battery is an air battery, it is easy to cause the problem of electrolyte composition change due to the evaporation of water in the aqueous electrolyte and the loss from the air holes. Therefore, from the viewpoint of avoiding such a problem, a water-soluble high boiling point solvent with a boiling point of 150°C or more (preferably 320°C or less) can be used together with water as a solvent for the aqueous electrolyte, or a thickener can be added to the aqueous electrolyte formed by the aqueous solution (more preferably, it is made into a gel (gel electrolyte)).
[0075] Examples of the water-soluble high boiling point solvent include polyols such as ethylene glycol (boiling point 197° C.), propylene glycol (boiling point 188° C.), and glycerol (boiling point 290° C.); polyalkylene glycols such as polyethylene glycol (PEG, for example, boiling point 230° C.) (preferably polyalkylene glycols having a molecular weight of 600 or less), etc. When a water-soluble high boiling point solvent is used, its proportion in the total solvent is preferably 3 to 30% by mass.
[0076] In addition, when using an aqueous electrolyte formed by an aqueous solution, there is a concern that the negative electrode with an electrolytic zinc foil as an active material layer may be broken due to corrosion caused by the aqueous electrolyte, and the capacity cannot be fully obtained. However, when a thickener is added to the aqueous electrolyte in advance, and it is more preferably made into a gel (gel electrolyte), it can not only avoid the above-mentioned problem of electrolyte composition change, but also suppress the undesirable corrosion reaction of the negative electrode, suppress the generation of gas associated with it, and suppress the occurrence of negative electrode breakage. As thickeners that can be added to the aqueous electrolyte, cellulose derivatives such as carboxymethyl cellulose (CMC) and carboxyethyl cellulose (CEC); polyoxyalkylene oxides such as polyethylene oxide (PEO) (wherein, preferably a molecular weight of 1000 or more, more preferably 10000 or more); polyvinyl pyrrolidone; polyvinyl acetate; starch; guar gum; xanthan gum; sodium alginate; hyaluronic acid; gelatin; various synthetic polymers or natural polymers such as polyacrylic acid are listed. Furthermore, among the above-exemplified thickeners, when using a thickener having a functional group formed by a carboxyl group or a salt thereof (-COOH, -COONa, etc.) in the molecule, it is preferred to add a polymetallic salt that acts as a gelation promoter to the aqueous electrolyte. In order to improve the above-mentioned effect, the amount of the thickener in the aqueous electrolyte is preferably 0.1% by mass or more, more preferably 1% by mass or more, and most preferably 3% by mass or more; in order to prevent the decrease in discharge characteristics, it is preferably 20% by mass or less, more preferably 15% by mass or less, and most preferably 10% by mass or less. In addition, when using a gelation promoter, in terms of mass ratio, when the proportion of the thickener is 100, the proportion of the gelation promoter is preferably 1 to 30.
[0077] When the sheet battery is a manganese battery, it is preferable to use an aqueous solution of zinc chloride as the aqueous electrolyte, and the concentration of zinc chloride is preferably 10 to 40% by mass.
[0078] The aqueous electrolyte solution may also be made into a gel state (gel electrolyte) using a known gelling agent such as a polymer.
[0079] <Sheet-shaped exterior body>
[0080] The sheet-like outer casing in the sheet-like battery may be made of a resin film. Examples of such resin films include nylon films (such as nylon 66 films) and polyester films (such as polyethylene terephthalate (PET) films).
[0081] It should be noted that the sealing of the sheet-like outer body is generally performed by heat-melting the end of the resin film on the upper side of the sheet-like outer body with the end of the resin film on the lower side. In order to make the heat-melting easier, a heat-melting resin layer can be laminated on the resin film exemplified above and used for the sheet-like outer body. As the heat-melting resin constituting the heat-melting resin layer, modified polyolefins (modified polyolefin ionomers, etc.), polypropylene and copolymers thereof, etc. are listed. The thickness of the heat-melting resin layer is preferably 20 to 200 μm.
[0082] In addition, a metal layer may be laminated on the resin film. The metal layer may be composed of an aluminum film (including aluminum foil and aluminum alloy foil), a stainless steel film (stainless steel foil), etc. The thickness of the metal layer is preferably 10 to 150 μm.
[0083] Furthermore, the resin film constituting the sheet-like exterior body may be a film in which the heat-sealed resin layer and the metal layer are laminated.
[0084] In addition, the resin film constituting the sheet-like exterior body preferably also has an electrically insulating water vapor barrier layer. In this case, it may be a single-layer structure in which the electrically insulating resin film itself also functions as a water vapor barrier layer, or a multilayer structure having a plurality of electrically insulating resin film layers, at least one of which functions as a water vapor barrier layer, or a multilayer structure having an electrically insulating water vapor barrier layer on the surface of a base layer formed of a resin film.
[0085] Among such resin films, it is preferable to use a resin film in which a water vapor barrier layer composed of at least an inorganic oxide is formed on the surface of a base layer composed of the resin film.
[0086] As the inorganic oxide constituting the water vapor barrier layer, aluminum oxide, silicon oxide, etc. are listed. It should be noted that the water vapor barrier layer composed of silicon oxide tends to have a higher function of inhibiting the permeation of water in the electrolyte in the battery than the water vapor barrier layer composed of aluminum oxide. Accordingly, silicon oxide is more preferably used as the inorganic oxide constituting the water vapor barrier layer.
[0087] The water vapor barrier layer composed of an inorganic oxide can be formed on the surface of the base layer by, for example, a vapor deposition method. The thickness of the water vapor barrier layer is preferably 10 to 300 nm.
[0088] The substrate layer of the resin film having the water vapor barrier layer may be a polyolefin film, a polyimide film, a polycarbonate film, etc. in addition to the above-mentioned nylon film and polyester film. The thickness of the substrate layer is preferably 5 to 100 μm.
[0089] When a resin film having a water vapor barrier layer and a substrate layer is formed, a protective layer for protecting the water vapor barrier layer may be formed on the surface of the water vapor barrier layer (the surface opposite to the substrate layer).
[0090] When a resin film having a water vapor barrier layer and a base material layer is formed, the above-mentioned heat-sealed resin layer may be further laminated.
[0091] The thickness of the entire resin film is preferably 10 μm or more from the viewpoint of providing sufficient strength to the sheet battery, and is preferably 200 μm or less from the viewpoint of suppressing an increase in the thickness of the sheet battery and a decrease in energy density.
[0092] The water vapor permeability of the resin film constituting the sheet-like outer casing is preferably 10 g / m 2 · 24h or less. It should be noted that the resin film is preferably as impermeable to water vapor as possible, that is, its water vapor permeability is preferably as small as possible, which can be 0 g / m 2 ·24h.
[0093] The water vapor permeability of a resin film referred to in this specification is a value measured based on JIS K 7129B method.
[0094] It should be noted that, in the case where the sheet battery is an air battery, the resin film constituting the sheet outer body preferably has a certain degree of oxygen permeability. Since the air battery supplies air (oxygen) to the positive electrode to discharge, an air hole for introducing oxygen into the battery is formed on the sheet outer body, but in the case where the resin film constituting the sheet outer body has oxygen permeability, oxygen can also be introduced into the battery from the position outside the air hole of the sheet outer body through the outer body, so that oxygen can be supplied to the entire positive electrode more evenly, the discharge characteristics of the battery can be improved, or the discharge time can be prolonged. In addition, a sheet air battery without air holes on the sheet outer body can also be realized.
[0095] When the sheet-shaped battery is an air battery, the specific oxygen permeability of the resin film constituting the sheet-shaped exterior body is preferably 0.02 cm 3 / m 2 ·24h·MPa or more, more preferably 0.2cm 3 / m2 However, in the case of air batteries, if the resin film constituting the sheet-like outer body is excessively permeable to oxygen, there is a concern that self-discharge may occur and the capacity may be impaired. Therefore, the oxygen permeability of the resin film is preferably 100 cm 3 / m 2 ·24h·MPa or less, more preferably 50cm 3 / m 2 ·24h·MPa or less.
[0096] On the other hand, when the sheet-shaped battery is a battery other than an air battery, there is no particular limitation on the oxygen permeability of the resin film constituting the sheet-shaped outer casing. From the viewpoint of improving the storage property of the battery, it is preferred that oxygen not be permeated much. Specifically, the oxygen permeability of the resin film is preferably 10 cm 3 / m 2 ·24h·MPa or less.
[0097] The oxygen permeability of the resin film referred to in this specification is a value measured based on the JIS K 7126-2 method.
[0098] Next, the sheet battery of the present embodiment will be described based on the drawings.
[0099] Figure 2 and Figure 3 An example of a sheet battery according to this embodiment is schematically shown. Figure 2 and Figure 3 For example, when the sheet battery is an air battery, Figure 2 Display its floor plan, Figure 3 show Figure 2 II line cross-sectional view.
[0100] like Figure 3 As shown, in the sheet-like battery 1, a negative electrode 10, a separator 30, a positive electrode 20, and an aqueous electrolyte (not shown) are accommodated in a sheet-like outer casing 50. Figure 2 The dotted line in φ indicates the size of the positive electrode 20 housed in the sheet-like outer package 50 (the size of the wider main body excluding the positive electrode external terminal, which corresponds to the size of the catalyst layer of the positive electrode).
[0101] The negative electrode external terminal 12 of the negative electrode 10 and the positive electrode external terminal 22 of the positive electrode 20 protrude from the upper side of the sheet-like outer package 50 in the figure. These external terminals 12 and 22 are used to electrically connect the sheet-like battery 1 to applicable equipment.
[0102] The sheet-like outer casing 50 has a plurality of air holes 51 for allowing air to enter the positive electrode on one side where the positive electrode 20 is arranged. A waterproof film 40 is arranged on the sheet-like outer casing 50 side of the positive electrode 20 to prevent the aqueous electrolyte from leaking from the air holes 51 .
[0103] The positive electrode 20 has a catalyst layer, and has a structure in which, for example, the catalyst layer and the current collector are stacked, as described above. Figure 3 In order to avoid complicating the drawings, the layers of the positive electrode 20 are not shown separately. Figure 3 In the figure, the sheet-like external package 50 (the resin film constituting the sheet-like external package 50) is shown as a single-layer structure, but as described above, the resin film constituting the sheet-like external package 50 may also be a multi-layer structure.
[0104] In the case where the sheet battery is an air battery, Figure 3 As shown, a waterproof membrane is arranged between the positive electrode and the outer body. The waterproof membrane can be a membrane that can pass air on the waterproof side. Specific examples of such a waterproof membrane include a membrane composed of a fluororesin such as PTFE; a membrane composed of a resin such as polypropylene, polyethylene, etc. The thickness of the waterproof membrane is preferably 10 to 250 μm.
[0105] In addition, when the sheet-shaped battery is an air battery, an air diffusion membrane for supplying air entering the outer casing to the positive electrode may be arranged between the outer casing and the waterproof film. The air diffusion membrane may be a nonwoven fabric made of a resin such as cellulose, polyvinyl alcohol, polypropylene, or nylon. The thickness of the air diffusion membrane is preferably 100 to 250 μm.
[0106] For the thickness of sheet batteries ( Figure 3 The length of a in the figure is not particularly limited and can be changed appropriately according to the purpose of the battery. It should be noted that one of the advantages of a battery having a sheet-like outer body (i.e., a sheet-like battery) is that it can be formed into a thin shape. From this point of view, its thickness is preferably, for example, less than 1 mm. When the sheet-like battery is an air battery, it is particularly easy to provide such a thin battery.
[0107] In addition, there is no particular restriction on the lower limit of the thickness of the sheet battery, but in order to ensure a certain capacity, it is usually preferably 0.2 mm or more.
[0108] The sheet battery of this embodiment can be used for the same purposes as the purposes of various sheet batteries known in the past, and is particularly suitable for power supplies for medical and health equipment represented by patches that can be worn on the skin surface for measuring body conditions such as body temperature, pulse, and sweating. In addition, the negative electrode of this embodiment can be used as a negative electrode of various batteries with an aqueous electrolyte, and is particularly useful as a negative electrode of a sheet battery.
[0109] Example
[0110] Hereinafter, the sheet-shaped battery disclosed in the present application will be described in detail based on examples. However, the sheet-shaped battery disclosed in the present application is not limited to the following examples.
[0111] Electrolytic zinc foils with a thickness of 50 μm and compositions shown in Table 1 and rolled zinc foils with a thickness of 50 μm and compositions shown in Table 2 were prepared and subjected to flexibility evaluation tests and gas generation measurement tests. It should be noted that the electrolytic zinc foils and rolled zinc foils contain inevitable impurities in addition to Zn and the elements shown in the table.
[0112] [Table 1]
[0113]
[0114] [Table 2]
[0115]
[0116] 〔Flexibility evaluation test〕
[0117] Electrolytic zinc foil C, electrolytic zinc foil D, rolled zinc foil K, rolled zinc foil N and rolled zinc foil O were cut into 30 mm × 15 mm sizes to prepare evaluation samples. The evaluation samples were bent 90 degrees in the middle of the longitudinal direction to check whether there was a crack in the middle.
[0118] Next, the evaluation sample was further bent so that both sides were in contact (180-degree bending), and the presence or absence of cracks in the center was confirmed.
[0119] Furthermore, the evaluation sample was bent in the opposite direction so that both sides were in contact (bent 180 degrees in the opposite direction), and the presence or absence of cracks in the center was confirmed.
[0120] In the electrolytic zinc foil C, the rolled zinc foil K, and the rolled zinc foil O, no cracks occurred during any bending, and the content of 800×10 -4 Electrolytic zinc foil D with mass% (800ppm) In broke at the 90-degree bending stage and contained 1000×10 -4 The rolled zinc foil N containing 1000 ppm of In by mass % broke when it was bent 180 degrees in the opposite direction.
[0121] The above results show that the inclusion of In in the electrolytic zinc foil tends to reduce the flexibility of the foil, and therefore, in order to ensure the productivity of the negative electrode and to make the battery formed into a sheet flexible, it is preferable to reduce the In content.
[0122] [Gas generation measurement test]
[0123] Electrolytic zinc foils A to H and rolled zinc foils K to P were cut into 60 mm × 20 mm sizes, and 5 mm width of the peripheral edges and cut surfaces of both sides were covered with adhesive tape to form exposed portions of zinc foil of 50 mm × 10 mm in the center of both sides to prepare evaluation samples.
[0124] The evaluation samples were constructed so that only the exposed portion of the zinc foil was in contact with the electrolyte, and were immersed in 15 g of an electrolyte consisting of a 20 mass % ammonium chloride aqueous solution. They were then kept at 60° C. for 24 hours, and the amount of hydrogen generated during the period was measured.
[0125] The measurement results are shown in Table 3. -4 The results for zinc foil with a mass % (4000 ppm) or less are shown in Figure 4 .
[0126] [Table 3]
[0127] Gas production (ml) Electrolytic zinc foil A 4 Electrolytic zinc foil B 0.53 Electrolytic zinc foil C 0.3 Electrolytic zinc foil D 0.42 Electrolytic zinc foil E 0.24 Electrolytic zinc foil F 0.46 Electrolytic zinc foil G 0.54 Electrolytic zinc foil H 0.85 Rolled zinc foil K 4.3 Rolled zinc foil L 3.4 Rolled zinc foil M 3.9 Rolled zinc foil N 0.89 Rolled zinc foil O 2.32 Rolled zinc foil P 1.58
[0128] For electrolytic zinc foil, by adding Bi, the amount of hydrogen generated can be greatly reduced compared to rolled zinc foil. According to the above results, by using electrolytic zinc foil as the active material layer of the negative electrode to form a battery, the storage characteristics of the battery can be greatly improved. On the other hand, for rolled zinc foil, it was found that the effect of adding Bi is limited, and In is more effective in reducing the amount of hydrogen generated, and its preferred form is different from that of electrolytic zinc foil.
[0129] 〔Discharge characteristics evaluation test〕
[0130] Next, sheet batteries were assembled using the electrolytic zinc foils A to C and E to G, and the discharge characteristics were evaluated.
[0131] (Example 1)
[0132] <Negative electrode>
[0133] Cut the electrolytic zinc foil A into Figure 1 A negative electrode for an aqueous electrolyte battery was produced in the shape shown (the dimensions of the main body are 15 mm long x 15 mm wide, and the dimensions of the negative electrode external terminal are 5 mm wide x 15 mm long).
[0134] <Positive electrode>
[0135] DBP oil absorption 495cm 3 / 100g, specific surface area 1270m 2 100 parts by mass of carbon black ("Ketchen Black EC600JD" (trade name) manufactured by Lion Specialty Chemicals) with a concentration of 1.17 g / g, 1 part by mass of a phthalocyanine metal complex, 25 parts by mass of a dispersant, and 5000 parts by mass of ethanol were mixed to prepare a catalyst layer-forming composition.
[0136] A porous carbon paper (thickness: 0.25 mm, porosity: 75%, air permeability (Gurley): 70 sec / 100 ml) was used as a current collector, and the catalyst layer-forming composition was applied in an amount of 10 mg / cm after drying. 2 The surface of the current collector is coated with a stripe pattern and dried to obtain a current collector having a portion where a catalyst layer is formed and a portion where a catalyst layer is not formed. The current collector is punched into a shape where the catalyst layer is 15 mm × 15 mm in size and one end of the collector has a portion where a catalyst layer is not formed and the size is 5 mm × 15 mm, which becomes the positive electrode external terminal, to produce a positive electrode (air electrode) with an overall thickness of 0.27 mm.
[0137] <Diaphragm>
[0138] The separator used was a separator (total thickness: 50 μm) in which a grafted film (thickness: 30 μm) composed of a graft copolymer having a structure in which acrylic acid was graft-copolymerized on a polyethylene main chain was arranged on one side of a cellophane film (thickness: 20 μm).
[0139] <Waterproof membrane>
[0140] As the waterproof membrane, a PE microporous membrane having a thickness of 75 μm was used.
[0141] <Aqueous electrolyte>
[0142] The aqueous electrolyte used was a solution prepared by dissolving 8% by mass of polyoxyethylene having an average molecular weight of 7,000,000 in a 20% by mass aqueous ammonium chloride solution (pH 4.3 measured at 25° C. using a “LAQUAtwin Compact pH Meter” manufactured by Horiba, Ltd.).
[0143] <Battery Assembly>
[0144] Two sheets of a commercially available barrier film ("GL FILM" manufactured by Toppan Printing Co., Ltd., thickness: 67 μm) cut into a size of 40 mm×35 mm were prepared and used as the outer package.
[0145] On one outer casing disposed on the positive electrode side, 9 air holes with a diameter of about 0.2 mm are regularly formed in a manner of 3 vertically and 3 horizontally at equal intervals (the distance between the centers of the air holes is 10 mm vertically and horizontally), and the waterproof film is heat-fused on the inner surface side using a hot melt adhesive resin. In addition, on the other outer casing disposed on the negative electrode side, a modified polyolefin ionomer film is installed parallel to the side of the outer casing at the portion where the external terminals of the positive and negative electrodes are disposed, in order to improve the sealing performance of the heat-fused portion between the external terminals and the outer casing.
[0146] With a sheet-like outer casing having a waterproof film as the bottom, the positive electrode, the separator and the negative electrode are sequentially stacked on the waterproof film of the outer casing, and then another outer casing is covered in such a manner that the modified polyolefin ionomer film is located on the leads of the positive electrode and the negative electrode. The separator is arranged in such a manner that the cellophane film faces the negative electrode. Next, the three sides of the two outer casings are heat-fused to each other to form a bag shape, the aqueous electrolyte is injected from the opening, and then the opening is heat-fused and sealed to make a sheet-like air battery.
[0147] (Example 2)
[0148] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the electrolytic zinc foil B was used to produce the negative electrode for the aqueous electrolyte battery.
[0149] (Example 3)
[0150] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the electrolytic zinc foil C was used to produce the negative electrode for the aqueous electrolyte battery.
[0151] (Example 4)
[0152] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the electrolytic zinc foil E was used to produce the negative electrode for the aqueous electrolyte battery.
[0153] (Example 5)
[0154] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the electrolytic zinc foil F was used to produce the negative electrode for the aqueous electrolyte battery.
[0155] (Example 6)
[0156] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the electrolytic zinc foil G was used to produce the negative electrode for the aqueous electrolyte battery.
[0157] The discharge characteristics of the sheet-shaped air batteries of Examples 1 to 6 were evaluated by the following method.
[0158] A discharge resistor of 3.9 kΩ was connected to each sheet-shaped air battery to discharge it, and the battery voltage (CCV) was measured when the discharge amount reached 10 mAh, thereby evaluating the discharge characteristics. The results are shown in Figure 5 .
[0159] Depend on Figure 5 The results show that if the Bi content of the electrolytic zinc foil constituting the negative electrode increases, the reaction resistance of the negative electrode during discharge increases and the operating voltage of the battery decreases. Therefore, from the perspective of the discharge characteristics of the battery, it is preferable to reduce the Bi content of the electrolytic zinc foil.
[0160] [Storage characteristics evaluation test]
[0161] (Comparative Example 1)
[0162] A sheet-shaped air battery was assembled in the same manner as in Example 1 except that the rolled zinc foil M was used to produce the negative electrode for an aqueous electrolyte battery.
[0163] The sheet-shaped air batteries of Examples 2 to 4 and Comparative Example 1 were evaluated for storage characteristics under the following conditions.
[0164] For each sheet-shaped air battery, an AC voltage of 1kHz was applied at room temperature to measure the internal resistance. Next, each sheet-shaped air battery was stored in an atmosphere at a temperature of 40°C for 35 days, cooled to room temperature, and then the internal resistance after storage was measured under the same conditions as above. Furthermore, a discharge resistor of 3.9kΩ was connected to each sheet-shaped air battery and discharged, and the discharge capacity until the battery voltage dropped to 1.0V was measured. The respective measurement results are shown in Table 4.
[0165] [Table 4]
[0166]
[0167] Since the sheet-like air batteries of Examples 2 to 4 are constructed using the battery negative electrode of this embodiment having an active material layer composed of electrolytic zinc foil, they have excellent storage characteristics compared to the sheet-like air battery of Comparative Example 1 which is constructed using the battery negative electrode having an active material layer composed of rolled zinc foil.
[0168] The present invention can be implemented in other ways than those described above without departing from the scope of its purpose. The embodiment disclosed in this application is only an example and is not limited thereto. The scope of the present invention is interpreted by the attached claims in priority to the description of the above specification, and all changes within the scope equivalent to the scope of the claims are included in the scope of the claims.
[0169] Explanation of symbols
[0170] 1: Sheet battery,
[0171] 10: Negative electrode,
[0172] 11: The main body of the negative electrode,
[0173] 12: Negative external terminal,
[0174] 20: positive electrode (air electrode),
[0175] 22: Positive external terminal,
[0176] 30: diaphragm,
[0177] 40: waterproof membrane,
[0178] 50: Flake outer body,
[0179] 51: Air hole.
Claims
1. A battery, characterized in that: The battery comprises an outer casing and a power generation element accommodated in the outer casing. The power generation elements include a positive electrode, a negative electrode, a separator and an aqueous electrolyte. The negative electrode contains an electrolytic zinc foil as an active material layer, wherein the electrolytic zinc foil is composed of a zinc alloy containing Bi in a ratio of 0.001 to 0.644 mass %. The aqueous electrolyte is an aqueous electrolyte having a pH of 3 or more and less than 12 or an alkaline electrolyte having a pH of 12 or more.
2. The battery according to claim 1, wherein The electrolytic zinc foil is made of a zinc alloy containing Bi at a ratio of 0.02 mass % or more.
3. The battery according to claim 1 or 2, wherein The electrolytic zinc foil is made of a zinc alloy containing Bi at a ratio of 0.2 mass % or less.
4. The battery according to claim 1 or 2, wherein The electrolytic zinc foil is made of a zinc alloy containing no In or containing In in a proportion of 0.04 mass % or less.
5. The battery according to claim 1 or 2, which has a thickness of 10 to 1000 μm.
6. The battery according to claim 1 or 2, wherein the negative electrode comprises a main body portion functioning as a negative electrode active material layer, a negative electrode external terminal, and a lead portion connecting the main body portion and the negative electrode external terminal. The main body, the negative electrode external terminal and the lead are integrally formed of the electrolytic zinc foil.
7. The battery according to claim 1 or 2, wherein: The pH of the aqueous electrolyte is less than 7.
8. The battery according to claim 1 or 2, wherein The positive electrode contains silver oxide or manganese oxide as a positive electrode active material.
Citation Information
Patent Citations
Air cell and patch
WO2018056307A1